Anomalous sudden drop of temperature-dependent Young's modulus of a plastically deformed duplex stainless steel. (5th November 2019) - Wang, Xu; Wan, Jianquan; Wang, Jianbiao; Zhu, Linli; Ruan, Haihui
Abstract: This work reports an anomalous and remarkable Sudden Drop of Modulus (SDM) associated with a precipitous surge of internal friction induced by the solid-state phase transformation (SSPT) in a severely cold-rolled duplex stainless steel (DSS). It is further shown that such a sudden drop does not appear if the DSS is not plastically deformed or if the severely rolled single-phase stainless steel is examined, indicating respectively that the phase growth or the recrystallization is not the cause. This anomaly occurs at the temperature between 930 and 950 °C, which is much lower than the solidus temperature of the DSS. And the results of differential scanning calorimetry (DSC) do not render any strong endothermic behavior at the temperature of SDM, excluding the possibility of pre-melting of some last solidified region. Based on these experimental results, we speculate that the SSPT in the severely deformed DSS may undergo a crystal-amorphous-crystal (CAC) two-step process, in which the intermediate amorphous phase with a low viscosity accounts for the sudden drop of the Young's modulus and the sudden surge of the internal friction. This amorphous phase is metastable, which gradually transforms to crystalline phase associated with a heat release and the slow recovery of stiffness. Graphical abstract: Unlabelled Image Highlights: The anomalous sudden drop of modulus of a duplex stainless steel at 950 °C is found. The unexpected surge of the internal friction associate with the drop of modulus is observed. DSC results indicate an exothermal behavior associated with the recovery of the modulus. A physical picture of the crystal-amorphous-crystal two-step transition is conceived.